The Existence of Ornamental Coral in Different Live Coral Coverage Condition in Saleh Bay, West Nusa Tenggara - Ofri Johan; Yulius Yulius; Hadiwijaya Lesmana Salim; Idil Ardi; Muhammad Abrar; August Daulat (Pusat Riset Kelautan, 2019)
Ornamental coral is one of the trading commodities targets with high demand in all of the world because of its color and unique shape. Various types of ornamental corals are usually found in a specific area and out of reach, where one of them situated in water depth that it so difficult to find. West Nusa Tenggara Province is known as one of the ornamental coral suppliers that has not been touched much by research related to the existence of ornamental coral natural resources. This study aims to obtain preliminary data on the existence of ornamental coral, especially in Saleh Bay waters. Observations carried out from 6 to 11 May 2015 at 6 locations, determined based on distance from the mainland with respective representation, which divided into categories such as near, medium and far using the straight-line transect methods for coral reefs condition, while belt transect methods used for ornamental corals assessment. The results showed the health of coral reefs in good condition with the cover above 50% at all stations except station 4 (medium category), where Acropora coral species dominated at stations 5 and 6 (distant category). The bottom substrate dominated by coral fragments and dead corals with algae (DCA), which are found 28 genera of ornamental corals and considered as trade commodities such as Euphyllia glabrescens, Euphyllia cristata, Euphyllia ancora, Echinophora sp, Gonioporasp, Lobophyllia sp, Physogyra sp, Merulina sp, and Turbinaria sp. The research location can be used as a permanent study area for ornamental coral focus subject and as an indicator for sustainable ornamental coral management in the region.